Reading up on Bookcrossing. - Eidenbenz, Raphael; Yu Li; Wattenhofer, Roger (International Journal of the Book, 2013)
"Bookcrossing" is the activity of depositing a book some place for others to find, pick up, and read. By analyzing the data of Bookcrossing--a website that, among other features, records the bookcrossing actions of its members--we study the paths that books take when they are bookcrossed. We investigate how the release location, language, genre, and review score of a book influence its journey. Moreover, we compare the bookcrossing data to the book market of Amazon to reveal special properties of the bookcrossing market.